Assessment of laser-assisted micromanipulation procedures in a commercial bovine in vitro production laboratory - Baroni, Jonas I (2021)
In vitro production (IVP) of bovine embryos is increasing yearly and is rapidly becoming the most commonly-used tool in cattle breeding. The drive for more efficient food production requires accelerated dissemination of superior cattle genetics. The implementation of advanced techniques such embryo biopsy and laser assisted hatching (LAH) with IVP embryos facilitates early genetic selection and could enhance pregnancy rates following embryo transfer. The nature and extent of chromosomal errors can also be established from embryo biopsies, and this could also improve pregnancy outcomes following embryo transfer. However, the techniques of bovine embryo biopsy and LAH are laborious, time consuming, utilise expensive equipment and require a high degree of technical skill. This thesis describes a series of experiments which sought to develop easy and robust methods for embryo biopsy and LAH in a commercial laboratory setting. It assessed the survivability and ‘hatchability’ of embryos compared to those that were not manipulated.